The Impact of Formative Assessment and Feedback on Student Engagement in an Economics Course - Wiwi Fitria Anjani; Friyatmi Friyatmi (Jurnal Inovasi Pendidikan Ekonomi, 2026)
Low student engagement, characterized by poor academic performance and widespread truancy, is a global challenge exacerbated by the dominance of conventional teaching methods. As an intervention, this study aims to analyze the effect of the quality of formative assessment and assessment feedback, both individually and simultaneously, on student engagement in economics classes. Using a quantitative associative-causal approach, data were collected via a questionnaire administered to a sample of 112 Phase E students at SMA Negeri 1 X Koto, selected through proportional stratified random sampling. The data were then analyzed using multiple linear regression. The results of the hypothesis testing confirmed that the quality of formative assessment and assessment feedback, when considered simultaneously, significantly enhanced student engagement (R² = 0.664, F = 107.546, p < 0.001). Partially, both variables also made positive and significant contributions, with formative assessment (β = 0.237, t = 2.147, p = 0.034, 95% CI [0.020, 0.505]) and assessment feedback (β = 0.601, t = 5.457, p < 0.001, 95% CI [0.261, 0.560]) each showing a significant effect, with assessment feedback emerging as the most dominant variable in enhancing student engagement in the classroom. This study concludes that the use of periodic evaluation instruments and the provision of constructive feedback can create an interactive classroom environment, thereby effectively transforming students from passive listeners into proactive and independent learners.